NOVEL TRANSETHOSOME CONTAINING GREEN TEA (CAMELLIA SINENSIS L. KUNTZE) LEAF EXTRACT FOR ENHANCED SKIN DELIVERY OF EPIGALLOCATECHIN GALLATE: FORMULATION AND IN VITRO PENETRATION TEST - Anwar, Effionora; Ramadon, Delly; Ardi, Ghina Desviyanti (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to formulate a transethosome cream (TEC) to increase skin penetration of epigallocatechin gallate (EGCG) in green tea leaf extract and evaluate their physicochemical characteristics and skin penetration capacity. Methods: Transethosomes were prepared through thin-layer hydration method in three formulations (F1−F3) with different Span 80 and ethanol concentrations. Transethosome morphology was characterized using transmission electron microscopy, particle size, polydispersity (PDI), and zeta potential using a particle size analyzer and entrapment efficiency (EE). Penetration was tested using an in vitro Franz diffusion cell with female Sprague-Dawley rat skin as the membrane. Results: Transethosome F2 containing green tea extract equivalent to 3% EGCG, 4% Lipoid P30, 0.75% Span 80, and 30% ethanol had the best characteristic including spherical shape, smallest particle size (35.35 nm), 0.319 PDI, zeta potential of −29.97±3.05 mV, and highest EE of 45.26%±8.15%. TEC permitted greater flux than non-TEC (first phase: 60.56±4.52 vs. 25.69±0.83 μg•cm−2•h−1 and second phase: 23.13±1.38 vs. 7.36±1.59 μg•cm−2•h−1). Conclusion: Transethosome can increase the skin penetration of green tea leaf extract.